The Effect of UGC Food Travel Sharing on Impulse Travel Intention: Based on Presence - Huang, Jingqi (Economics & Management Review, 2024)
Given the thriving nature of food-related content on the Internet and its influential role in promoting destinations tourism, coupled with the widespread utilization of presence in social media , this study introduces the notion of presence and endeavors to elucidate the impact of user-generated content centered around food on social media platforms on impulsive travel intentions from the perspective of presence. By constructing a conceptual model, this study employed a questionnaire survey to gather feedback data on the sense of presence, arousal, positive emotions, and impulse travel intention of individuals following their viewing of a food introduction video,then subsequently verified the structural equation model. The findings indicate that the sense of presence evoked by user generated food travel sharing significantly influences arousal, positive emotions, and impulse travel intention. However, the impact of arousal and positive emotions on travel intention is not statistically significant. Consequently, the sense of presence emerges as a pivotal driving factor in social media marketing for tourist destinations.